La pena di morte come trasgressione dei fondamentali diritti umani in Occhio per occhio di Sandro Veronesi - Kłosek, Wiesława (Romanica Silesiana)
The book Occhio per occhio by Sandro Veronesi is an important voice in the ongoing discussion on death penalty. First published in 1992 in the form of an essay, it was republished in 2004 as a prose narrative. Veronesi combines journalistic style with narrative fiction and thus reaches a the wide range of readers. The key word to the analysed text is “transgression.” Veronesi shows four countries which represent four sides of the world as well as very different political and cultural systems. He shows similar mechanisms of violation of certain norms and laws in these countries. The title of his work, which refers to the Biblical law of retaliation, clearly determines the position of the author who sees death penalty as a tool of revenge. Veronesi does not speak to the reader from the position of a detached theoretician, but as a man who personally experienced the tragedy of people affected by death penalty. For the reason that the author assumes a definitive position in the discussion and refers to a general concept of human nature, his novel arouses emotions and evokes controversies. Key words: Death penalty, human rights, transgression, the right to retaliate, contemporary Italian Prose.